Development of Methodologies and Software for Design, Simulation and Optimization of Oil Hydraulic Cylinders of Large Dimensions and Power - Stefan Cvejić; Radovan Petrović; Maja Andjelković; Ivana Ilić; Vjačeslav Mutavči; Ana Radosavljević Mihajlović; Mladen Vuruna (Applied Sciences, 2024)
As part of the research carried out in the field of processing systems and the production process of oil-hydraulic cylinders of large dimensions and power, the specifics of fluid power transmission, in the functioning of hydropower facilities, were analyzed. The research also includes the optimization of the physical–mathematical model of non-stationary processes, which take place inside the chamber of a large hydrocylinder. In parallel with the definition of the optimization model, the work parameters that affect the process of fluid flow and piston movement were determined. The operating and technological construction parameters of the hydraulic cylinder, which most significantly affect the operation of the hydraulic cylinder, were defined, and the observed parameters were optimized, based on which a prototype with improved characteristics compared to existing solutions was realized.